PENYERAHAN DAN BIMBINGAN TEKNIS PENGGUNAAN MESIN PENGHANCUR BIJI BIJIAN - Rizki Ramdani; Agus Saleh; Gerinata Ginting; Yoddy Agung Nuhgraha; Riri Damayanti Apnena; Eva Damayanti; Elvathna Syafwan (ASOSIASI IDEBAHASA KEPRI, 2022)
The process that has been carried out in providing chicken feed for livestock is by providing ready-to-use or ready-to-use feed. Prepared feed on the market of course has a relatively more expensive price, compared to raw feed which must be processed first. Milled corn on the market has a relatively more expensive price, compared to corn ore. Ways that can be done to overcome the problems above, namely by implementing or applying technology (machine) in the feed processing process.